PENGARUH PENGETAHUAN MENDETEKSI KEKELIRUAN, PENGALAMAN AUDITOR, PROFESIONALISME AUDITOR, DAN RISIKO AUDIT TERHADAP PENENTUAN TINGKAT MATERIALITAS - Susanto, Vinsen Revelin; Kristanto, Septian Bayu (Jurnal Penelitian Akuntansi (JPA), 2025)
The purpose of this study to analyze the influence of knowledge of error detection, auditors’ experience, professionalism, and audit risk on materiality-level considerations. This study uses primary data collected from questionannaire using google form as the tools to help collect data by broadcasting it through email and peers. The population of this study is auditors who works at accounting firms in the city of Jakarta and the sampling technique used for this study is purposive sampling, there are two requirment for the sample and it needs to meet both requirments, which is they are an auditor that works at accounting firms in the city of Jakarta and at one point make a judgement to set the materiality level on financial statement level or on account level. The type of data used in this study is quantitative with multiple linear reggresion to analyze the relation between variables. The results show that knowledge of error detection, auditors’ experience, professionalism, and audit risk simultaneously have a significant influence on materiality-level considerations. Knowledge of error detection, auditors’ experience, professionalism, and audit risk partially have a positive and significant influence on materiality-level considerations.